Ergonomic Evaluation of Manual Weeders - Kumar, Adarsh; Tandon, S K; Saxena, J P (Journal of Agricultural Engineering, 2002)
Three types of manual weeders namely wheel hoe, crescent hoe and kasola (a spade type tool) were ergonomically evaluated. The performance in respect of the area coverage, overall discomfort and body part discomfort were evaluated. The highest field capacity was observed in wheel hoes. At the overall discomfort score of 4 i.e. "very tired", in all the cases, output of work was 108.21 sq m, 66.74 sq m and 58 sq m and body part discomfort score was 29.5, 26.22 and 23.22 for wheel hoe, crescent hoe and crescent hoe and kasola respectively. There was significant difference in the area covered by wheel hoe and the other two hoes whereas overall tiredness and body part discomfort score were non-significantly different among different weeders.